A Power Efficient Self Biased OTA Design Based on g_m/I_D Methodology with Considering Load Variation, Temperature Variation and Power Supply Variation - Vikas Mittal (International Journal of Reconfigurable and Embedded Systems (IJRES), 2018)
The present work addresses the design of power efficient fully self biased OTA using a design methodology based on the  transistor characteristics. This analog module was analyzed, designed and prototyped in TSMS 0.35μm CMOS technology. Simulation results are presented, in order to validate the methodology. The OTA has Gain of 41.35 dB and 3db bandwidth of 138.73 kHz and the UGB of 12.40MHz with the current consumption of 65.50 μA. The circuit does not have need of any DC external biasing circuit, only need to apply VDD (3.3 V). Here self biasing has been introduced with power consumption of 216.15μW. The results have been taken with load variations, temperature variations, and power supply variations. This circuit used in real time high frequency applications as in RF communication.